Effect of non-invasive ventilation on respiratory muscle loading and endurance in patients with Duchenne muscular dystrophy. Issue 5 (5th December 2007) - Toussaint, M; Soudon, P; Kinnear, W
Abstract : Background: Respiratory muscle weakness in patients with Duchenne muscular dystrophy (DMD) leads to respiratory failure for which non-invasive positive pressure ventilation (NIPPV) is an effective treatment. This is used initially at night (n-NIPPV) but, as the disease progresses, diurnal use (d-NIPPV) is often necessary. The connection between NIPPV and relief of respiratory muscle fatigue remains unclear. A study was undertaken to determine the extent to which n-NIPPV and d-NIPPV unload the respiratory muscles and improve respiratory endurance in patients with DMD. Methods: Fifty patients with DMD were assessed at 20.00 and 08.00 h. More severely affected patients with nocturnal hypoventilation received n-NIPPV; those with daytime dyspnoea also received d-NIPPV via a mouthpiece (14.00–16.00 h). Lung function, modified Borg dyspnoea score, spontaneous breathing pattern, tension-time index (TT0.1 = occlusion pressure (P0.1 )/maximum inspiratory pressure (MIP) × duty cycle (Ti/Ttot)) and respiratory muscle endurance time (Tlim) against a threshold load of 35% MIP were measured. Results: More severe respiratory muscle weakness was associated with a higher TT0.1 and lower Tlim. In contrast to non-dyspnoeic patients, patients with dyspnoea (Borg score >2.5/10) showed an increase in Tlim and decrease in TT0.1 after n-NIPPV. At 16.00 h, immediately after d-NIPPV, patients with dyspnoea had lower TT0.1 and Borg scores with unchanged Tlim. Compared with the control day without d-NIPPV, TT0.1, Borg scores and Tlim were all improved at 20.00 h. Conclusions: In patients with dyspnoea with DMD, the load on respiratory muscles increases and endurance capacity decreases with increasing breathlessness during the day, and this is reversed by n-NIPPV. An additional 2 h of d-NIPPV unloads respiratory muscles and reverses breathlessness more effectively than n-NIPPV alone.